Three new foliicolous ascomycetes from Kerala - T.K. ABRAHAM, V.B. HOSAGOUDAR and (Indian Phytopathology, 2002)
Three new species of foliicolous ascomycetes, Asterina lycianthedis, A. melicopecola and Asterinella jasmini, collected from the Neyyer Wildlife Sanctuary, Kerala State, India, during 1996 are described and illustrated.